Effect of Peripheral Velocity Difference Ratio on the Performance of Rubber Roll Huske - Shitanda, Douglas; Nishiyama, Y.; Koide, S. (The Japanese Society of Agricultural Machinery and Food Engineers, 2000)
The difference in speed between the rubber rolls results in a shearing action on the rice grain as it passes between the rolls (Yamashita et al 1990, FA, 1995). The shearing force is thus dependent on the relative velocity between the rolls and the normal force. The normal force is generally determined by the clearance between the rolls. Since energy is a very significant part of the rubber husker performance, consideration of its influencing factors is vital.
Keywords: Peripheral velocity difference ratio; Husked ratio; Roken ratio; Cracked ratio; Husker